2021
DOI: 10.1186/s40621-021-00324-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the lockdown executive order during the COVID-19 pandemic in recent trauma admissions in Puerto Rico

Abstract: Background The COVID-19 pandemic led to world-wide restrictions on social activities to curb the spread of this disease. Very little is known about the impact of these restrictions on trauma centers. Our objective was to determine the effect of the pandemic-associated lockdown on trauma admissions, patient’s demographics, mechanisms of injury, injury severity, and outcomes in the Puerto Rico Trauma Hospital. Methods An IRB-approved quasi-experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
2
6
0
Order By: Relevance
“…The increase in trauma surgical procedures occurred in the second half of the first wave of the COVID-19 pandemic. This increase may result from an increase in falls and household injuries, which was seen in other studies ( 25 , 26 , 27 ). Additionally, an increase in bicycle accidents during the lockdown, as described previously, may be attributed to the increase in surgical trauma procedures as well ( 27 ).…”
Section: Discussionsupporting
confidence: 60%
“…The increase in trauma surgical procedures occurred in the second half of the first wave of the COVID-19 pandemic. This increase may result from an increase in falls and household injuries, which was seen in other studies ( 25 , 26 , 27 ). Additionally, an increase in bicycle accidents during the lockdown, as described previously, may be attributed to the increase in surgical trauma procedures as well ( 27 ).…”
Section: Discussionsupporting
confidence: 60%
“…When considering mortality rates, we found no significant difference between the groups. This finding was consistent with other studies in the literature [ 7 , 12 , 15 , 16 ]. Also, ICU admissions and surgical intervention rates were similar in this study.…”
Section: Discussionsupporting
confidence: 94%
“…But Yeates et al found an increase in gunshot wounds after COVID-19 stay-at-home advisories [ 15 ]. In another study conducted on this subject, it was emphasized that traumas due to falls increased and other trauma mechanisms decreased during the COVID-19 pandemic [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another current 2021 report has likewise shown that there has been an increase in home injuries over the pandemic period, and that falls remained the dominant mechanism of injury in 2020 in this regard, contributing 39.9% of all hospitalizations according to Christey et al [9]. Ruiz-Medina et al [10] too reported falls rates to have experienced a significant increase during the lockdown period (18.9% vs. 26.7%; p = 0.026).…”
Section: Introductionmentioning
confidence: 98%